PENGEMBANGAN MEDIA KOMIK PINTAR (KOMPA) PADA TEMA 3 PEDULI TERHADAP MAKHLUK HIDUP UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS IV SD NEGERI 104211 MARINDAL - Rizka Wahyuni Harahap; Samsul Bahri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to find out how the development of smart comic book-based learning media (Kompa) in thematic learning theme 3 cares for living things sub-theme 1 animals and plants in my home environment, determines the level of validity of the media and increases the learning motivation of class IV students at SD Negeri 104211 Marindal . This research is a type of Research and Development (R&D) research. The model used in this development is the ADDIE model. The ADDIE model is a development model that has five stages, namely analysis, design, development, implementation, and evaluation. Research limits only to 3 stages, namely the development stage. The subjects in this study were the validation of material experts, media experts, learning experts (teachers) and fourth grade elementary school students, totaling 22 students, while the object of this study was the development of smart comic media (Kompa) on theme 3 caring for living things, fourth grade students at school base. Based on the results of the calculations for the learning media above, the results of the assessment from material experts obtained 87.24% with very valid and feasible criteria for use in learning while the assessment results from media experts obtained 84% with very valid criteria and suitable for use in learning. The results of the practicality of learning media for the teacher's response obtained a value of 96%, and for student responses it obtained 97.04%, meaning that the media criteria were very practical. Based on the data obtained, it can be concluded that smart comic media (Kompa) is stated to be very valid and very practical and can increase students' learning motivation at SD Negeri 104211 Marindal.